Magnet effect of price limits: evidence from Bursa Malaysia - Mohammad Sifat, Imtiaz; Mohamad, Azhar (2017)
Since the late 1980s it has become a common practice worldwide—especially in frontier markets—to impose price limits on stock prices, effectively stunting its intraday growth or decline beyond a certain bracket. Ostensibly, its purport is to prevent investor overreaction, regulatory control of market micro-structure, prevention of crash, and to smoothen excessive volatility. The most ubiquitous form of circuit breaker is price limit, which is used in equity and futures markets. The ranges of existing price limits vary geographically and from exchange to exchange. Academics and regulators have divergent opinions on application of circuit breakers and its resultant positive or negative effects. To put it concisely, the efficacy of circuit breakers is hotly disputed and evidence is still inconclusive for either camp. A lot of academic studies claim circuit breakers have the opposite of intended effects—i.e. they result in attracting prices to the limits by their very existence and thus defeating the volatility tempering objective. Utilizing Historical daily price from 1994 till 2017 in Bursa Malaysia, we employ two logistic regression models to check whether magnet effect exists. Having divided the study period into 3 distinct regimes based on regulatory limit mechanisms, we find evidence of strong magnet effect in Bursa Malaysia throughout the period, which was especially pronounced between 2002 and 2013. Also, for all samplings, we find magnet effect more accentuated for upper limit scenarios.